Congruency between Word Position and Meaning is Caused by Task-Induced Spatial Attention - Pecher, Diane; Van Dantzig, Saskia; Boot, Inge; Zanolie, Kiki; Huber, David E. (Frontiers in Psychology, 2010)
We report an experiment that compared two explanations for the effect of congruency between a word’s on screen spatial position and its meaning. On one account, congruency is explained by the match between position and a mental simulation of meaning. Alternatively, congruency is explained by the polarity alignment principle. To distinguish between these accounts we presented the same object names (e.g., shark, helicopter) in a sky decision task or an ocean decision task, such that response polarity and typical location were disentangled. Sky decision responses were faster to words at the top of the screen compared to words at the bottom of the screen, but the reverse was found for ocean decision responses. These results are problematic for the polarity principle, and support the claim that spatial attention is directed by mental simulation of the task-relevant conceptual dimension.